Human Needs as an Approach to Designed Landscapes - Aly, Dalia; Hassan, Doaa K.; Mohamed Kamel, Shaimaa; Hamhaber, Johannes (JNRD - Journal of Natural Resources and Development, 2018)
The traditional approach of landscape architecture has always focused on the aesthetic and visual aspects of landscapes while giving less attention to other aspects. This view has limited the benefits that can be derived from designed landscapes, despite the wide-ranging potential they carry for humans; socially, environmentally and economically. As a result, many researchers and practitioners are currently challenging this view to develop a more holistic and multidimensional approach. The present research therefore aims at proposing a new perspective for public designed landscapes based on fundamental human needs. The study methodology was comprised of critical content analysis for three main domains: sustainable development, human needs in specific relation to public landscapes, and significant approaches to fundamental human needs. Reconciliation among these domains was achieved based on a modified version of Max-Neef’s matrix of fundamental human needs. Human needs in public landscapes were merged into the matrix to reach a comprehensive yet specific perspective. The study concluded with a conceptual framework that can provide a wider perspective to human needs in designed landscapes. It proposes a new tool for the analysis of the benefits of public landscapes and their value for humans, which can be further used in various applications.